When the road is rocky: Investigating the role of vulnerability in consumer journeys - Sudbury-Riley, Lynn; Hunter-Jones, Philippa; Al-Abdin, Ahmed; Haenlein, Michael (Journal of the Academy of Marketing Science, 2024)
AbstractJourney research has primarily analyzed agentic, solo travelers making rational single-purchase decisions. In contrast, we examine a journey where consumers and their traveling companions are vulnerable and must navigate an unfamiliar service system. We explore how vulnerability shapes consumer journeys, how service and system factors impact vulnerability, and how traveling companions influence agency and vulnerability. Using data from an extensive study into end-of-life care, our results reveal novel insights into the role of consumer vulnerability throughout a journey. We show how the ebb and flow of consumer vulnerability shapes the journey, and how the journey shapes vulnerability. Traveling companions, themselves vulnerable, play a major role in influencing vulnerability and the journey itself. We offer managerial implications for organizations whose consumers are in vulnerable situations.